In silico and ADMET/Pharmacokinetics Prediction Studies of Some Novel Pyrido-Pyrimidine Derivatives as Anticancer - Yadav, Pratibha; Shah, Kamal (International Journal of Pharmaceutical Investigation, 2025)
Objectives To investigate the mechanism of pyridopyrimidines derivatives against monopolar spindle1 anticancer target and also predicts the pharmacokinetics parameters involved absorption, distribution, metabolism, elimination and toxicity (ADMET). Materials and Methods One hundred fifty pyridopyrimidines derivatives had been designed and analyzed for drug- likeness. The molecular docking of the entire designed scaffold was performed to protein target. Then the molecular interaction was performed with individual derivative, after that ADMET properties have been predicted. Results Drug-likeness results showed that all the designed pyridopyrimidine derivatives were within the range by Lipinski’s rule of five. This study predicted that pyridopyrimidines had potential as an anticancer agent acting via inhibiting MPS-1 target (PDB ID-6H3K). The predicted derivatives which had shown better activity in terms of binding affinity than reference ((palbociclib) were P4, P7, P8 and P13.These compounds had also good ADMET properties. Conclusions Molecular docking and ADMET analyses revealed that pyridopyrimidine derivatives demonstrate promising anticancer potential by effectively targeting MPS1. These compounds engage the MPS1 kinase domain primarily through hydrogen bonds supporting their candidacy as novel MPS1 inhibitors.
Keywords: Cancer; Pyrido-pyrimidines; MPS1; in silico study ADME-T/pharmacokinetics etc